The Effect of Capital Adequacy Ratio (CAR), Non Performing Financial (NPF), and Quick Ratio (QR) on Return on Asset (ROA) of BNI Syariah - Ekananda, Ricko; R Jayaprawira, Acep (The Indonesian Journal of Business Administration, 2017)
Abstract – Bank soundness should be maintained to deal with banking-related risks such as credit risk, liquidation risk, and interest risk. Credit risk is a risk that arises due to the customer’s inability to pay the debt and the interest within the adjusted time. Liquidation risk is a risk that a bank may face in providing credits and saving withdrawals of its customers at a particular time.  Risk of interest rate occurs when bank receives deposit with high interest rate for a longer period that the interest rate undergoes sudden and drastic fall. When a bank has relatively high funding, it will make it uncompetitive. Besides, the success of banking business is determined by its managerial performance in keeping its customers’ financial issues secret and keeping their money and assets safe.According to (Siamat, 2005:275), bank runs its business by collecting money from the society and distributing it in the forms of alternative investments. Because of this function, bank is also called the institution of trust. In reference to its business characteristic, bank is a business segment which activities are mostly regulated by the government. Bank stands as financial intermediary. It links parties who hold funds and those who need funding. It also facilitates payment traffic. Since bank runs its business on people’s trust, the level of bank soundness should be maintained (Merkusiwati, 2007). Banking plays an important role in accomplishing national goals that are related to the improvement and equal distribution of social life rate as well as in supporting the economy since it functions as an intermediary board, the administrator of payment transaction, and the transmitting means of monetary policy. According to Law of Republic of Indonesia Number 10 of 1998 concerning Banking, bank is regarded as a business institution that collects money from society in the forms of deposits and distributes the money to the society in the forms of loan and other products in order to improve the social life of rate. Bank’s financial report is composed as the manifestation of managerial liability towards the stakeholders within a particular period of time (Taswan, 2003:37). Bank’s performance can be measured by using many methods. The prominent method is by using financial ratio analysis; it is used for identifying any aspects that affect the financial position and development of the bank (Rohmawati, 2003:21). Assessment of banking financial performance has been adjusted by Bank Indonesia by issuing the Decree of Director of Bank Indonesia Number 30/11/KEP/DIR on 19th of March 1998 concerning the administration of Bank Soundness Assessment. Bank soundness assessment is managed y using one of financial performance indicators that is Return on Asset (ROA). ROA can be measured by comparing the profit prior to tax to the total assets. When ROA indicates that the financial performance is fine, the rate of return will be higher as well. In addition to that, bank soundness can be measured from the financial ratios of bank, such as Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), and Quick Ratio (QR).